Strategi Pengembangan Usahatani Kopi Arabika (Kasus pada Petani Kopi Di Desa Suntenjaya Kecamatan Lembang Kabupaten Bandung Barat, Provinsi Jawa Barat) - Akhmad Zakaria; Pingkan Aditiawati; Mia Rosmiati (Jurnal Sosioteknologi, 2017)
Coffee is an important export commodity for Indonesia, which is able to contribute a sizeable foreign exchange. West Bandung Regency is a regency in West Java province which have significant potential for the development of Arabica coffee commodity. Suntenjaya village, Lembang district is one of the Arabica coffee-producing areas in West Bandung regency. However, there are some obstacles in the development of arabica coffee farming including land resources utilization, harvest and post-harvest, quality and institutional aspects. Therefore, it is necessary to formulate business development strategies that can be applied arabica coffee farmers. Data and information needed were primary data and secondary data. Data were analyzed using SWOT analysis and QSPM. The study concluded that in order to help farmers in developing a business, there are several strategies a priority that can be conducted, that is  develop the processing of product, improve technical skills of farming to increase product quality, empowerment of farmer to further improve the business, increasing access to capital, optimize of farming business land, optimizing production capacity and maintain marketing network. Keywords: arabica coffee, SWOT analysis, coffee farming, the development strategy